2020
DOI: 10.1007/s12633-020-00657-1
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Tunnel Field-Effect Transistor (TFET) Based Biosensors: Recent Advances and Future Prospects on Device Structure and Sensitivity

Abstract: In this fast-growing technological world biosensors become more substantial in human life and the extensive use of biosensors creates enormous research interest among researchers to define different approaches to detect biomolecules. The FET based biosensors have gained a lot of attention among all because of its high detection ability, low power, low cost, label-free detection of biomolecules, and CMOS compatible on-chip integration. The sensitivity of the biosensor inversely proportional to device size since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…5a to Fig. 5f [35]. The surface of channel is applied with negative QF of −0.110 12 cm -2 , −0.510 12 cm -2 , and −110 12 cm -2 to mimic the different concentrations of target biomolecules [28].…”
Section: Application Of Interface Charge Densities For Difference Channel Widthsmentioning
confidence: 99%
See 1 more Smart Citation
“…5a to Fig. 5f [35]. The surface of channel is applied with negative QF of −0.110 12 cm -2 , −0.510 12 cm -2 , and −110 12 cm -2 to mimic the different concentrations of target biomolecules [28].…”
Section: Application Of Interface Charge Densities For Difference Channel Widthsmentioning
confidence: 99%
“…These results show that all the simulated SiNW (InPNW) channel doping is affected by the application of different Q F values applied on them, hence indicate that the SiNW (InPNW) channel detect different target analyte concentrations that will be captured by the bioreceptor immobilized onto the device. The detection will be signified by the relative change in ID, which is the percentage difference of ID before and after detection [35]. InPNW -FET graph for biosensors at different channel doping of 0.1×10 14 cm -3 , 1×10 14 cm -3 , 10×10 14 cm -3 when applied with different Q F of −0.110 12 cm -2 , −0.510 12 cm -2 , and −1.010 12 cm -2 .…”
Section: Application Of Interface Charge Densities For Difference Channel Dopingmentioning
confidence: 99%
“…The conventional FET size is scaled down to improve the performance in terms of speed and power consumption but it is limited and restricted due to the encounter of the short channel effects (SECs) and high leakage current. The fundamental limitation on the minimum achievable subthreshold swing (SS > 60mv/dec) and the SCEs are treated as the major setback for the improvement of performance for the CFET‐based biosensors 11,12 …”
Section: Introductionmentioning
confidence: 99%
“…Many researchers were impressed and inspired by the FET-based biosensors' characteristics, carried out immense research, and reported a good and fruitful development in FET-based biosensors. The performance of the FET-based biosensors is high in class, but still, they are beyond touching the tip of the sensitivity because of the following hectic issues (1) the theoretical constraint on the minimum achievable subthreshold slope (SS > 60mv/dec) due to Boltzmann tyranny [KBT/q ln (10)] and (2) the short channel effects experience by the FET device in the process of curtailing and scaling [8].…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, the tunnel field-effect transistor (TFET) has become a prominent substitute to the CFET by employing a distinct and unique carrier transport mechanism bandto-band tunneling form source to channel with a minimal gate voltage [8][9][10]. The TFET can exhibit a superior subthreshold swing (SS < 60 mv/dec), which is the key performance metric for designing highly efficient biosensors.…”
Section: Introductionmentioning
confidence: 99%